FIKSASI GARAM SCARLET R PADA PEWARNAAN KAIN SONGKET PALEMBANG BERBASIS ZAT WARNA ALAM DAUN HENNA (Lawsonia inermis L.) - Luftinor Luftinor (Balai Riset dan Standardisasi Industri Palembang, 2017)
Scarlet R salt has been used as a fixation material on staining process of cotton yarn and silk yarn in Palembang songket making using natural henna leaf coloring (Lawsonia inermis L) by varying the concentration of henna leaf extract in 4 treatment levels 20 g / l each, 40 g / l, 60 g / l and 80 g / l and varying the scarlet salt fixation solution R of 1 g / l, 4 g / l, 7 g / l and 10 g / l respectively, to obtain 16 kinds of songket Parameters analyzed include color darkness, color fastness to washing, rubbing, sweat and light. The objective of the study was to obtain the best treatment of the coloring process performed, while the overall test result fulfilled the SNI quality requirements of color fastness test for washing, sweat and rubbing (BSN, 1989), except the results of testing the color fastness to light. The best treatment was obtained at the concentration of leaf extract of henna 60 g / l and the concentration of scarlet salt fixation R 7 g / l on silk songket fabric resulted in color K / S 21.65, color fastness against washing value 4 (good) for change Color and 4-5 (good) for color staining, color fastness against rubbing 4-5 value (good) for dry rub and 3-4 (enough) for wet rub, color fastness to sweat value 4-5 (good) For acid and base sweat and color fastness to light values of 2-3 (less).